The Segmentation of Local Television Audiences in Central Java in the Digital Era - Warto, Warto (Universitas Semarang, 2019)
This theme of this article is the audiences segmentation by local television in Central Java. This study is motivated by the large amount of number of local television stations that have sprung up, as the digital era progresses. This study uses qualitative descriptive approach with the sample of five television stations, namely Banyumas TV, Semarang TV, TVKU Semarang, Simpang5 TV Pati, and also Ratih TV Kebumen. The target of the audiences segmentation demographically is the people aged 30 years and above, except TVKU Semarang, namely teenagers and students aged 15-25 years. The development in the digital era is now an opportunity to maintain the existence of local television by doing convergence of digital media. The concept of Think Global Act Local is the opposite in the local television industry to become Think Local Act Global , for the broadcasting world if they still want to exist in the digital media.